(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the article the forms and contents of the literary works of some Uzbek and English writers’ literary works (fictions) are analyzed by means of some examples taken from the works of “Utkan kunlar” (“Bygone days”) and “Robinson Crusoe”